If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(-3k + -5) + 9(8 + -1k) = 5k + 5k + 7 + 3k Reorder the terms: 12(-5 + -3k) + 9(8 + -1k) = 5k + 5k + 7 + 3k (-5 * 12 + -3k * 12) + 9(8 + -1k) = 5k + 5k + 7 + 3k (-60 + -36k) + 9(8 + -1k) = 5k + 5k + 7 + 3k -60 + -36k + (8 * 9 + -1k * 9) = 5k + 5k + 7 + 3k -60 + -36k + (72 + -9k) = 5k + 5k + 7 + 3k Reorder the terms: -60 + 72 + -36k + -9k = 5k + 5k + 7 + 3k Combine like terms: -60 + 72 = 12 12 + -36k + -9k = 5k + 5k + 7 + 3k Combine like terms: -36k + -9k = -45k 12 + -45k = 5k + 5k + 7 + 3k Reorder the terms: 12 + -45k = 7 + 5k + 5k + 3k Combine like terms: 5k + 5k = 10k 12 + -45k = 7 + 10k + 3k Combine like terms: 10k + 3k = 13k 12 + -45k = 7 + 13k Solving 12 + -45k = 7 + 13k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-13k' to each side of the equation. 12 + -45k + -13k = 7 + 13k + -13k Combine like terms: -45k + -13k = -58k 12 + -58k = 7 + 13k + -13k Combine like terms: 13k + -13k = 0 12 + -58k = 7 + 0 12 + -58k = 7 Add '-12' to each side of the equation. 12 + -12 + -58k = 7 + -12 Combine like terms: 12 + -12 = 0 0 + -58k = 7 + -12 -58k = 7 + -12 Combine like terms: 7 + -12 = -5 -58k = -5 Divide each side by '-58'. k = 0.08620689655 Simplifying k = 0.08620689655
| 6:00+41/2= | | x*3=76 | | 6y+20=80 | | 9x^2+36x+20=0 | | 3,5x+8=2(x+7) | | 5a+15a=100 | | 4x^2-15x+10=-4x+4 | | -11n-10n=2(n-3)-2(12+4n) | | 5/8=15/24 | | -11=m+12m | | x^2-x-18=-2x+2 | | 5x+7=7x+27 | | 3/7=6/15 | | 6xsquare-37x=-6 | | 20m-14=10 | | 2(4+3m)=3 | | 2,5(x-2)-1,5x=1 | | 3(k+5)=-8 | | (X-4)=15 | | 6=(1/2)(5)(x) | | 2m+18=6m | | -5(10+2x)-2(x+4)=14 | | 9=8*-5+8 | | 2y/3-8=2y+3 | | -9(5-4x)-(3x+5)=49 | | 2(m+4)=6 | | -4(10-8y)=24 | | k/2-4=-7 | | 5(x+2)=4(x-6) | | 2x^(3/2)=250 | | 7x^8-7=0 | | 2(7-w)-4=0 |